Optimizing the Career Studies of Sharia Accounting Students in Madura with a SWOT Analysis Approach - Handayani, Sri; Purnamawati, Anni Muslimah; Andini, Fariza; Wirawan, Feby Ramzi (IAIN Kudus, 2024)
This study aims to investigate the career studies of Sharia accounting students inMadura and the challenges they face in pursuing their careers. The approach utilizedqualitative research through interview and observation techniques, employing a SWOTanalysis provides a comprehensive framework to identify internal and external factorsaffecting students' career potential. Therefore, numerous suggestions are made. First,universities and graduates must make concerted efforts to educate and socializecompanies and agencies about the exceptional quality of sharia accounting graduates.Secondly, the government must promote the expansion of the Sharia finance industry byimplementing regulations and policies, thereby creating new employment opportunitiesfor Sharia accounting graduates. Third, the government must promote the expansion ofthe Sharia finance industry through policies and regulations. This research is examinethe career studies of sharia accounting students, as well as the obstacles and challengesthey faced in achieving their career objectives.